The Effects of Tai Chi on the Renal and Cardiac Functions of Patients with Chronic Kidney and Cardiovascular Diseases - Shi, Zhi-Min; Liu, Fu-Rong; Wen, Hai-Ping; Yao, Chun-Xia (Journal of Physical Therapy Science, 2014)
[Purpose] To assess the effects of Tai Chi on the renal and cardiac functions of patients with chronic kidney disease (CKD) and cardiovascular disease (CVD). [Subjects and Methods] Twenty-one patients with CKD and CVD were randomly divided into control and exercise groups. The exercise group performed Tai Chi training for 30 minutes three to five times a week for 12 weeks, while the control group did not. All patients’ renal and cardiac functions and blood lipid parameters were measured at baseline and after 12 weeks. [Results] The 12 weeks Tai Chi intervention improved the estimated glomerular filtration rate (eGFR), left ventricular ejection fraction (LVEF), and the high density lipoprotein (HDL) level, and decreased the serum creatintine (Scr) level, heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and the total cholesterol (CH), triglyceride (TG) and low density lipoprotein (LDL) levels. The change in eGFR correlated negatively with the changes in CH, TG and LDL, and positively with the change in HDL. In addition, the change in SBP correlated positively with the changes in CH, TG and LDL, and negatively with the change in HDL. [Conclusion] Tai Chi training might improve the renal and cardiac functions of CKD and CVD patients via improved regulation of lipid metabolism.